2018
DOI: 10.1007/s10433-018-0475-2
|View full text |Cite
|
Sign up to set email alerts
|

It’s “the Joneses”: the influence of objective and subjective socioeconomic status on subjective perceptions of aging

Abstract: Positive subjective perceptions of aging predict various well-being, physical health, mental health, and longevity outcomes. Thus, it is important to consider what factors contribute to their formation. Socioeconomic status (SES) has been hypothesized to be one such factor, but past research has been mixed. We propose that subjective assessments of SES may better predict subjective perceptions of aging than traditional objective measures (e.g., income and education). The purpose of this study was to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 48 publications
9
45
0
Order By: Relevance
“…This may be due to older individuals having a poorer health status than younger individuals (Aarts et al, 2012;Barnett et al, 2012). We also found that being male predicts fewer AARC gains and more AARC losses both in the AARC-10 SF and in the AARC-50 cognitive functioning subscale (Dolan, Peasgood, & White, 2008;English et al, 2019;Miche et al, 2014) and this may be due to males being less actively focused on positive changes compared to females (Kaminski & Hayslip, 2006;Moore, 2010). Indeed, research shows that positive experiences of aging among females outweigh negative experiences, despite females being aware of significant changes in their body due to menopause (Hvas, 2006).…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…This may be due to older individuals having a poorer health status than younger individuals (Aarts et al, 2012;Barnett et al, 2012). We also found that being male predicts fewer AARC gains and more AARC losses both in the AARC-10 SF and in the AARC-50 cognitive functioning subscale (Dolan, Peasgood, & White, 2008;English et al, 2019;Miche et al, 2014) and this may be due to males being less actively focused on positive changes compared to females (Kaminski & Hayslip, 2006;Moore, 2010). Indeed, research shows that positive experiences of aging among females outweigh negative experiences, despite females being aware of significant changes in their body due to menopause (Hvas, 2006).…”
Section: Discussionmentioning
confidence: 56%
“…We found that the demographic variables age, gender, marital status, employment, and university education explain some variability in levels of AARC. We found that being older predicts fewer AARC gains and more AARC losses both in the AARC-10 SF and in the AARC-50 cognitive functioning subscale (English et al, 2019). This may be due to older individuals having a poorer health status than younger individuals (Aarts et al, 2012;Barnett et al, 2012).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations